miR-208a-3p Suppresses Osteoblast Differentiation and Inhibits Bone Formation by Targeting ACVR1 - Yasir Arfat; Muhammad Asim R. Basra; Muhammad Shahzad; Kashif Majeed; Nasir Mahmood; Hina Munir (Elsevier, 2018)
Emerging evidence indicates that many microRNAs (miRNAs) are indispensable regulators of osteoblast differentiation and bone formation. However, the role of miRNAs in mechanotransduction of osteoblasts remains to be elucidated. This study aimed to identify a mechanosensitive miRNA that regulates Activin A receptor type I (ACVR1)-induced osteogenic differentiation. After 4 weeks of hindlimb unloading (HLU) suspension of 6-month-old male C57BL/6J mice, femurs and tibias were harvested to extract total bone RNAs. Elevated levels of miR-208a-3p correlated with a lower degree of bone formation in whole-bone samples of HLU mice. However, in vitro overexpression of miR-208a-3p inhibited osteoblast differentiation, whereas silencing of miR-208a-3p by antagomiR-208a-3p promoted expression of osteoblast activity, bone formation marker genes, and matrix mineralization under mechanical unloading condition. Bioinformatics analysis and a luciferase assay revealed that ACVR1 is a target gene of miR-208a-3p that negatively regulates osteoblast differentiation under mechanical unloading environment. Further, this study also demonstrates that in vivo pre-treatment with antagomiR-208a-3p led to an increase in bone formation and trabecular microarchitecture and partly rescued the bone loss caused by mechanical unloading. Collectively, these results suggest that in vivo, inhibition of miRNA-208a-3p by antagomiR-208a-3p may be a potential therapeutic strategy for ameliorating bone loss.